Mechanisms of Change: A Population-Based Perspective on the Roles of Modularity and Pleiotropy in Diversification - Lewis, James J.; Van Belleghem, Steven M. (Frontiers in Ecology and Evolution, 2020)
Developmental modularity has long been viewed as a hierarchical organization that facilitates evolution through modification or reuse of preexisting modules. More recently, developmental modularity has been proposed as a mechanism capable of driving rapid evolution of novel color pattern phenotypes between closely related taxa. In this scenario, recombination between modular cis-regulatory elements (CREs) generates novel phenotypes by shuffling genetic variation at preexisting color pattern modules into new arrangements. Recent functional evidence from Drosophila flies and Heliconius butterflies, however, provides a series of examples in which CREs function in multiple developmental contexts and are thus highly pleiotropic. The potential prevalence of pleiotropy in CRE function could be a barrier to the proposed importance of CRE modules as a mechanism for rapid evolutionary change. Here we review the concept of developmental modularity, some examples that suggest developmental modularity underlies pattern evolution, and recent evidence that indicates modular CREs may be less common than previously expected. This leads us to suggest that alternative, non-modular hypotheses should be considered alongside proposals of modular CREs. We then propose the concept of evolutionary modularity as a specific alternative to developmental modularity when discrete, seemingly modular, phenotypes occur in hybridizing taxa. We suggest that evolutionary modularity provides a potentially important pathway for exchange of phenotypic elements between hybridizing taxa independent of the underlying developmental architecture.